18F- based quantification of the osteogenic potential of hMSCs - Großner, Tobias; Haberkorn, Uwe; Gotterbarm, Tobias (International journal of molecular sciences, 2020)
In bone tissue engineering, there is a constant need to design new methods for promoting in vitro osteogenic differentiation. Consequently, there is a strong demand for fast, effective and reliable methods to track and quantify osteogenesis in vitro. In this study, we used the radiopharmacon fluorine-18 (18F) to evaluate the amount of hydroxylapatite produced by mesenchymal stem cells (MSCs) in a monolayer cell culture in vitro. The hydroxylapatite bound tracer was evaluated using µ-positron emission tomography (µ-PET) scanning and activimeter analysis. It was therefore possible to determine the amount of synthesized mineral and thus to conclude the osteogenic potential of the cells. A Student’s t-test revealed a highly significant difference regarding tracer uptake between the osteogenic group and the corresponding control group (µ-PET p = 0.043; activimeter analysis p = 0.012). This tracer uptake showed a highly significant correlation with the gold standard of quantitative Alizarin Red staining (ARS) (r2 = 0.86) as well as with the absolute calcium content detected by inductively coupled plasma mass spectrometry (r2 = 0.81). The results showed that 18F labeling is a novel method to prove and quantify hydroxyapatite content in MSC monolayer cultures. The mineral layer remains intact for further analysis. This non-destructive in vitro method can be used to rapidly investigate bone tissue engineering strategies in terms of hydroxylapatite production, and could therefore accelerate the process of implementing new strategies in clinical practice.